Application of Geographic Information Systems (GIS) for Health Data Management in Kalipecabean Village: Enhancing Public Health Interventions - Andi Patriadi; Jaka Purnama; Paschal Rumihin (International Conference of Innovation and Community Engagement, 2024)
This study focuses on the development of a thematic map using Geographic Information Systems (GIS) to assist Kalipecabean Village officials in monitoring and managing public health conditions. The current mapping system lacked the necessary detail to identify the locations of healthcare service points and specific health issues, such as maternal health, elderly care, and stunting prevalence. Through consultations with village officials and data collection from healthcare posts, both spatial and non-spatial data were integrated into a comprehensive thematic map. This map provides a clear visualization of health conditions across the village, enabling more targeted and efficient healthcare interventions. The map was created in both printed and digital formats, with the digital version allowing for regular updates and access via online platforms. The implementation of GIS has enhanced the village’s ability to manage public health data securely, minimizing the risks of data loss. However, challenges related to the training of village officials in GIS usage and the availability of technological infrastructure need to be addressed for long-term sustainability. The results of this study demonstrate the effectiveness of GIS-based thematic mapping in improving public health monitoring and resource allocation in rural areas, offering a model for other communities facing similar challenges